Development of Student Worksheets (LKPD) assisted by the Liveworksheets Site to Increase Learning Motivation in Accounting Materials - Faradisa, Faradisa; Suarman, Suarman; Gusnardi, Gusnardi (FKIP-Universitas Riau, 2023)
This study aims to develop Student Worksheets (LKPD) to increase student motivation in accounting material for class X Accounting 1 SMK Muhammadiyah 2 Pekanbaru majoring in Accounting and Financial Institutions. This development research uses the ADDIE model, namely analysis, design, development, implementation and evaluation . Data collection techniques used interviews, LKPD validation instruments and materials, learning motivation instruments and student response instruments. Data analysis techniques used LKPD expert validation sheets and material experts. The results showed that the feasibility value of LKPD experts got an average score of 97 in the very decent category. As for the feasibility value of material experts, it gets an average score of 92 with a very decent category. Student responses showed 80.5 in the very useful category and the teacher's opinion stated that it was useful. This is also shown from the learning motivation of students increased with significance = 0.000 less than the 0.05 significance level. Based on expert assessments and student learning motivation after using the liveworksheets site-assisted LKPD it can be shown that the liveworksheets site-assisted LKPD that has been developed in general can be declared feasible to use.